Improving the Air Force Scientific Discovery Mission : leveraging best practices in basic research management : a workshop report (The National Academies Press, 2015)
"In 2014, the Air Force Studies Board conducted two workshops to review current research practices employed by the Air Force Office of Scientific Research (AFOSR). Improving the Air Force Scientific Discovery Mission summarizes the presentation and discussion of these two workshops. This report explores the unique drivers associated with management of a 6.1 basic research portfolio in the Department of Defense and investigates current and future practices that may further the effective and efficient management of basic research on behalf of the Air Force."--